2006
DOI: 10.1063/1.2357552
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet photoluminescence from Gd-implanted AlN epilayers

Abstract: Deep ultraviolet emission from gadolinium ͑Gd͒-implanted AlN thin films has been observed using photoluminescence ͑PL͒ spectroscopy. The AlN epilayers were ion implanted with Gd to a total dose of ϳ6 ϫ 10 14 cm −2 . Using the output at 197 nm from a quadrupled Ti:sapphire laser, narrow PL emission was observed at 318 nm, characteristic of the trivalent Gd ion. A broader emission band, also centered at 318 nm, was measured with excitation at 263 nm. The PL emission intensity decreased by less than a factor of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…The first part is the sharp lines seen at around 3.95 eV. These sharp lines are in agreement with previous research [2] and other results [3][4][5][6][7], and are assigned to be the emission lines due to the intra-transition from 6 P 7/2 to 8 S 7/2 of the Gd 3+ 4f electrons. The emission intensity decreases while increasing the Gd fraction ratio.…”
Section: Contributedsupporting
confidence: 87%
See 1 more Smart Citation
“…The first part is the sharp lines seen at around 3.95 eV. These sharp lines are in agreement with previous research [2] and other results [3][4][5][6][7], and are assigned to be the emission lines due to the intra-transition from 6 P 7/2 to 8 S 7/2 of the Gd 3+ 4f electrons. The emission intensity decreases while increasing the Gd fraction ratio.…”
Section: Contributedsupporting
confidence: 87%
“…GaN does not have enough bandgap as a host material for Gd. On the other hand, in the case of Al 1-x Gd x N there are several cathodoluminescence (CL) [2][3][4][5], electroluminescence [6], and photoluminescence (PL) [7] properties, and in this case every result shows a sharp line at 3.90 ~ 3.94 eV which is clearly observed and is well assigned to the 6 P 7/2 → 8 S 7/2 4f intra transition of Gd 3+ . However, the electronic structure of Al 1-x Gd x N is still not clear.…”
mentioning
confidence: 86%
“…In particular, the optical efficiency of ZnO is not reduced by Gd incorporation, as the first excitation level of 4f in Gd 3+ ion is above the band gap. 36 Therefore, no efficient energy can be transferred from electron-hole recombination in ZnO to 4f levels, and therefore, no reduction in bandage emission occurs due to energy transfer. 36 The RT absorption measurements were carried out for ZnO NRs grown at P(O2) = 200 mTorr (since this sample exhibits PL dominated by NRs emission) as shown in Fig 9b. It can be observed that the ZnO NRs band gap is red shifted (~3.22 eV), compared to bulk ZnO (3.37 eV at RT), 65 may be due to tensile stress.…”
Section: Growth Mechanismmentioning
confidence: 99%
“…In particular, gadolinium (Gd) dopants do not reduce the optical efficiency of ZnO NRs. 36 99.75 wt% pure ZnO (99.999%) powder with 0.25 wt% Gd2O3 (99.99%) powder (Sigma-Aldrich-US). A pellet with a diameter of 2.5 cm was pressed and sintered at ~ 1100  C for 12 h to produce a dense, 2.3-cm-diameter disc.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation and energy relaxation in Gd-doped AlN have been investigated by several groups. [6][7][8] centers. After relaxing the energy, the emission occurs from the lowest excited state.…”
Section: Introductionmentioning
confidence: 99%